Dendritic cell-targeted protein vaccines: a novel approach to induce T-cell immunity - Trumpfheller, C.; Longhi, M. P.; Caskey, M.; Idoyaga, J.; Bozzacco, L.; Keler, T.; Schlesinger, S. J.; Steinman, R. M. (Journal of internal medicine, 2012)
.  Trumpfheller C, Longhi MP, Caskey M, Idoyaga J, Bozzacco L, Keler T, Schlesinger SJ, Steinman RM (The Rockefeller University, New York, NY; and Celldex Therapeutics, Phillipsburg, NJ; USA). Dendritic cell‐targeted protein vaccines: a novel approach to induce T‐cell immunity (Review). J Intern Med 2012; 271: 183–192. Current vaccines primarily work by inducing protective antibodies. However, in many infections like HIV, malaria and tuberculosis as well as cancers, there remains a need for durable and protective T‐cell immunity. Here, we summarize our efforts to develop a safe T‐cell–based protein vaccine that exploits the pivotal role of dendritic cells (DC) in initiating adaptive immunity. Focusing on HIV, gag‐p24 protein antigen is introduced into a monoclonal antibody (mAb) that efficiently and specifically targets the DEC‐205 antigen uptake receptor on DC. When administered together with synthetic double‐stranded RNA, polyriboinosinic:polyribocytidylic acid (poly IC) or its analogue poly IC stabilized with carboxymethylcellulose and poly‐L‐lysine (poly ICLC), as adjuvant, HIV gag‐p24 within anti‐DEC‐205 mAb is highly immunogenic in mice, rhesus macaques, and in ongoing research, healthy human volunteers. Human subjects form both T‐ and B‐cell responses to DC‐targeted protein. Thus, DC‐targeted protein vaccines are a potential new vaccine platform, either alone or in combination with highly attenuated viral vectors, to induce integrated immune responses against microbial or cancer antigens, with improved ease of manufacturing and clinical use.